ความรู้ เจตคติ และการปฏิบัติของหัวหน้าห้องปฏิบัติการชันสูตรทางคลินิกกลางในการจัดการของ เสียอันตรายของโรงพยาบาลขนาดกลาง และขนาดใหญ่ในประเทศไทย พ.ศ. 2543 - ภูวนารถ หมู่พยัคฆ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
The purpose of this descriptive study was to determine knowledge, attitude, and practice of central clinical laboratory chiefs about hazardous waste management in medium and large hospitals in Thailand, 2000. The subjects were all of 245 central clinical laboratory chiefs. The pre-tested questionnaires were used. The data were collected by mailing questionnaires during 7 December, 2000 and 15 February, 2001. There were 161 respondents (response rate 65.7 %), consisted of 119 medium hospitals (73.9 %), and 42 large hospitals (26.1 %). Unpaired t-test and One-Way ANOVA were used for statistical analyses. The result of this study showed that the central clinical laboratory chiefs were female more than male (1.14 : 1). The mean age was 39.70 years. The majority of them got bachelor degree (77.0 %). Average of experience of central clinical laboratory chiefs was 11.45 years. Most of them were working in government hospital (64.6 %) , and technical medical science officers (85.8 %), but not trained about hazardous waste management in clinical laboratory (89.8 %). Knowledge of central clinical laboratory chiefs was rather low (48.5 %), attitude was good (82.5%) and practice was rather good (74.9 %). Knowledge and attitude of central clinical laboratory chiefs were not significantly associated with education level, the program they graduated, experience of central clinical laboratory chiefs, training, size of hospital, affiliation of hospital, amount of hazardous waste generated, and laboratory quality assurance system. Practice of central clinical laboratory chiefs were significantly associated with experience of central clinical laboratory chiefs, affiliation of hospital, and laboratory quality assurance system (p=0.019, 0.017 and 0.009, respectively). These results suggest that the knowledge and practice about hazardous waste management of central clinical laboratory chiefs should be improved by training on hazardous waste management, developing laboratory assurance system and integrating contents into curricula which teach about laboratory of high school through university.